Digital Image Chaotic Encryption (DICE - A partial-symmetric key cipher for digital images) - Kaushik, Akhil; Satvika; Gupta, Krishan; Kumar, Anant (2014 International Conference on Reliability Optimization and Information Technology (ICROIT), 2014)
The swift growth of communication facilities and ever decreasing cost of computer hardware has brought tremendous possibilities of expansion for commercial and academic rationales. With widely incremented communiqué like Internet, not only the good guys, but also bad guys have advantage. The hackers or crackers can take advantage of network vulnerabilities and pose a big threat to network security personnel. The information can be transferred by means of textual data, digital images, videos, animations, etc and thus requires better defense. Especially, the images are more visual and descriptive than textual data; hence they act as a momentous way of communication in the modern world. Protection of the digital images during transmission becomes more serious concern when they are confidential war plans, top-secret weapon photographs, stealthy military data and surreptitious architectural designs of financial buildings, etc. Several mechanisms like cryptography, steganography, hash functions, digital signatures have been designed to provide the ultimate safety for secret data. When the data is in form of digital images; certain features of images like high redundancy, strong correlation between neighbouring pixels and abundance in information expression need some extra fortification while transmission. This paper proposes a new cryptographic cipher named Digital Image Chaotic Encryption (DICE) to convene the special requisites of secure image transfer. The strength of DICE lies in its partial-symmetric key nature i.e. even discovery of encryption key by hacker will not guarantee decoding of the original message.